Selective Sharing of News Items and the Political Position of News Outlets - Julian Freitag; Anna Kerkhof; Johannes Münster (Center for Economic Studies and Ifo Institute (CESifo), 2021)
We present a new measure for the political position of news outlets based on politicians' selective sharing of news items. Politicians predominantly share news items that are in line with their political position, hence, one can infer the political position of news outlets from the politicians' revealed preferences over news items. We apply our measure to twelve major German media outlets by analyzing tweets of German Members of Parliament (MPs) on Twitter. For each news outlet under consideration, we compute the correlation between the political position of the seven parties in the 19th German Bundestag and their MPs' relative number of Twitter referrals to that outlet. We find that three outlets are positioned on the left, and two of them are positioned on the right. Several robustness checks support our results. We also apply our procedure to nine major media outlets from the USA and find that two outlets are positioned on the right, five are positioned on the left of the political spectrum.
Keywords: H41; L82; L86; P16; 330; political media bias; political position; selective sharing; social media; Twitter